2021
DOI: 10.2147/cia.s325035
|View full text |Cite
|
Sign up to set email alerts
|

How a Patient Personalised Clinical Pharmacy Programme Can Secure Therapeutic Care in an Orthogeriatric Care Pathway (5P Project)?

Abstract: Background: A new model was developed for integrating a personalised clinical pharmacy programme (5P project) into the orthogeriatric care pathway. Objective: To secure the therapeutic care of orthogeriatric patients. Design and Setting: Prospective descriptive study in a multisite teaching hospital from June 2019 to January 2020. Subjects: Patients aged ≥75 years admitted for hip fracture. Methods: A prescription review was performed for all patients at inclusion. Other clinical pharmacy activities (additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
5
1
Order By: Relevance
“…The average number of detected UID was consistent compared to other studies with hip‐fractured patients 22 or geriatric patients 23 . One can wonder whether all PI were clinically relevant from a medical point of view, which is why a full‐blown analysis of the potential clinical impact of PI has been performed 15 …”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The average number of detected UID was consistent compared to other studies with hip‐fractured patients 22 or geriatric patients 23 . One can wonder whether all PI were clinically relevant from a medical point of view, which is why a full‐blown analysis of the potential clinical impact of PI has been performed 15 …”
Section: Discussionsupporting
confidence: 79%
“…23 One can wonder whether all PI were clinically relevant from a medical point of view, which is why a full-blown analysis of the potential clinical impact of PI has been performed. 15 The present study showed a quite low number of information transmission to primary care actors at discharge. Nevertheless, community and rehabilitation structure pharmacists had a high satisfaction rate.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations